2021
DOI: 10.1111/nmo.14300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic restraint stress and western‐diet feeding on colonic regulatory gene expression in mice

Abstract: Background Diet‐induced obesity (DIO) and psychological stress are significant independent regulators of gastrointestinal physiology; however, our understanding of how these two disorders influence the host‐microbe interface is still poorly characterized. The aim of this study was to assess the combined influences of diet‐induced obesity and psychological stress on microbiome composition and colonic gene expression. Methods C57BL/6J mice (n = 48) were subject to a combination of 22 weeks of Western diet (WD) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 102 publications
(201 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the composition of the gut microbiota in unstressed female mice fed a high fat diet has been shown to resemble that of female mice exposed to CUMS, but fed a standard diet; however, the same effect is not observed in males, thus females may be more susceptible to the potential negative effects of high fat diets on the gut-brain axis [93]. Hatton-Jones et al [111] showed a Western diet decreased colonic tight junction protein expression in male mice, but this did not result in increased depressive-like behaviour and these effects were not synergistic with those of CRS. Yet, Ranyah Shaker et al [148] demonstrated male Wistar rats fed a high-fat diet had increased dopamine and glutamate, but decreased serotonin in the brain, with increased circulating IL-6 in association with decreased Clostridium and Bacteroides abundance.…”
Section: Diet Stress and Intestinal Barrier Integritymentioning
confidence: 99%
“…Interestingly, the composition of the gut microbiota in unstressed female mice fed a high fat diet has been shown to resemble that of female mice exposed to CUMS, but fed a standard diet; however, the same effect is not observed in males, thus females may be more susceptible to the potential negative effects of high fat diets on the gut-brain axis [93]. Hatton-Jones et al [111] showed a Western diet decreased colonic tight junction protein expression in male mice, but this did not result in increased depressive-like behaviour and these effects were not synergistic with those of CRS. Yet, Ranyah Shaker et al [148] demonstrated male Wistar rats fed a high-fat diet had increased dopamine and glutamate, but decreased serotonin in the brain, with increased circulating IL-6 in association with decreased Clostridium and Bacteroides abundance.…”
Section: Diet Stress and Intestinal Barrier Integritymentioning
confidence: 99%